Along-wind buffeting responses of wind turbines subjected to hurricanes considering unsteady aerodynamics of the tower. (1st May 2017) - Amirinia, Gholamreza; Jung, Sungmoon
Highlights: Unsteady aerodynamic analysis of the wind turbine tower was addressed in NREL-FAST. Frequency dependent admittance function was addressed by rational functions. Hurricane turbulence models was investigated and applied for unsteady analysis. Unsteady analysis of hurricane models changes the responses by 4.9%–29%. Abstract: Most of the studies on wind turbine subjected to high winds, consider quasi-steady formulation for wind turbine parts. The objective of this paper is to investigate the along wind responses of a parked wind turbine subjected to hurricane forces by considering, first, the tower unsteady aerodynamics, and second, the recent observations and proposed models for hurricanes. For this purpose, quasi-steady formulation of aerodynamic forces on a parked wind turbine was modified by addressing unsteady aerodynamic effects on the wind turbine tower. A time domain approach for addressing the unsteady aerodynamics of the tower was proposed by using aerodynamic admittance function. The frequency dependent aerodynamic admittance function was addressed in time domain using rational functions (RF). This procedure was implemented in NREL-FAST package and the model was verified. In order to investigate the structural responses subjected to hurricane, the recent observations of the hurricane boundary layer winds as well as the models presented for hurricane turbulence energy were discussed. The unsteady analysis of wind turbine structure subjected to various hurricane turbulence models, resulted in the range of 29% smaller to 4.9% larger responses than quasi-steady analysis of conventional spectrum models presented in past literature and carried out by NREL-FAST module.